Gross Motor Skills of The Childrenâs Group A Judging From Demonstration Method of Motion and Song in Kindergarten Pertiwi Nusa Indah - Komputerisna, Adzannisa Arum; Diana, Diana (BELIA: Early Childhood Education Papers, 2016)
Gross motor skills can be developed through a variety of interesting ways, one of them using a demonstration of motion and song. Demonstration method of motion and the song is a method that combines motion demonstration accompanied by the song to practice gross motor skills of children. The aim of this study was to determine differences in gross motor skills of children in group A in terms of methods of demonstration of motion and song. This study used an experimental method, with samples in TK Pertiwi Nusa Indah as an experimental class and TK Pertiwi Flamboyan as the control class. The method used is the method Quasi-experimental design types of nonequivalent control group design. Results of t-test calculation of independent sample t-test obtained t count equal to -17.318 with Sig. (2.tailed) <0.05, namely 0.00 <0.05. Based on the conclusion that there are differences in gross motor skills of children in group A in terms of methods of demonstration of motion and songs in kindergarten Nusa Pertiwi Indah. The conclusion that H0 is rejected and Ha accepted.